2018
DOI: 10.1103/physrevlett.121.130601
|View full text |Cite
|
Sign up to set email alerts
|

Unified Thermodynamic Uncertainty Relations in Linear Response

Abstract: Thermodynamic uncertainty relations (TURs) are recently established relations between the relative uncertainty of time-integrated currents and entropy production in nonequilibrium systems. For small perturbations away from equilibrium, linear response (LR) theory provides the natural framework to study generic nonequilibrium processes. Here we use LR to derive TURs in a straightforward and unified way. Our approach allows us to generalize TURs to systems without local time reversal symmetry, including, for exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 59 publications
(181 reference statements)
4
121
0
Order By: Relevance
“…We now explore how to relate the diffusion coefficient to efficiency. Recent works have shown that, in nonequilibrium dynamics, the current fluctuations are bounded by the coarse-grained entropy production rate [37][38][39][40][41]. In active fluids, there is no average current of particles provided that no asymmetric external potential is applied [68][69][70].…”
Section: Efficiency and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…We now explore how to relate the diffusion coefficient to efficiency. Recent works have shown that, in nonequilibrium dynamics, the current fluctuations are bounded by the coarse-grained entropy production rate [37][38][39][40][41]. In active fluids, there is no average current of particles provided that no asymmetric external potential is applied [68][69][70].…”
Section: Efficiency and Transportmentioning
confidence: 99%
“…While several works have strived to predict how internal transport is affected by activity [30][31][32][33][34][35], a recent study has put forward an explicit connection between diffusion and dissipation in a mixture of active and passive particles [36]. Moreover, for generic driven systems, it has been shown recently that the diffusion coefficient is generically bounded by dissipation [37][38][39][40][41]. Yet, this thermodynamic uncertainty relation (TUR) explicitly involves observable currents, thus being mostly useful for systems exhibiting directed transport.…”
Section: Introductionmentioning
confidence: 99%
“…which is independent of temperature. Following the inequality (14), it is straightforward to show that the TUR is satisfied in the co-tunneling limit. In fact, the NESB model behaves similarly to the harmonic junction in the co-tunneling limit since ∆ > T ν .…”
Section: Non-equilibrium Spin-boson Model: Tur Violation For Strumentioning
confidence: 99%
“…A connection between discrete and continuous time uncertainty relations is shown in [34]. One can also see similar uncertainty relations in the context of discrete processes [35], multidimensional systems [36], Brownian motion in the tilted periodic potential [37], general Langevin systems [38], molecular motors [39], run and tumble processes [40], biochemical oscillations [41], interacting oscillators [42], effect of magnetic field [43], linear response [44], measurement and feedback control [45], information [46], underdamped Langevin dynamics [47], timedelayed Langevin systems [48], various systems [49], etc.. Recently, Hasegawa et al [50] found an uncertainty relation for the time-asymmetric observable for the system driven by a time-symmetric driving protocol using the steady state fluctuation theorem.…”
Section: Introductionmentioning
confidence: 87%